Efektivitas Larutan Nabati Daun Paku Sisik Naga (Drymoglossum piloselloides) Terhadap Mortalitas Kutu Daun (Aphid) Pada Tanaman Kacang Panjang - Putra, Fernando Afrianto; Sari, Wilna; Putri, Santi Diana; Amelia, Kiki (JURNAL AGROPLASMA, 2025)
One of the pests that attack long bean plants is aphid. Aphid pest control can uce herbal insecticides, namely herbal solutions derived from dragon scale fern leaves. Dragon scale fern leaves contain flavonoids, saponins, phenolics, essential oil and tannins. This study aims to determine the effect of herbal solutions of dragon scale fern leaves on the mortality of aphid in long bean plants and to determine the dose of herbal solutions of dragon scale fern leaves that are effective against the mortality of aphid in long bean plants. The method used in this study is the completely Randomized Design (CRD) method with 5 treatments and 4 replications, namely the control treatment of water/aquadest, 35ml, 45ml, 55ml, 65ml of dragon scale fern leaf herbal solution . Observations were made every day for 168 hours/7 days. The research data are presented in the form of graphs/tables. The result of quantitative observations were analyzed using Analysis of Variance. There was a significant difference between the effects of the treatments tested, s further testing was carried out using Ducan’s Multiple Range Test (DMRT) at a level of 5%. The P4 dose treatment (65ml of dragon scale fern leaft herbal solution) is the best and most effective treatment/dose for aphid mortality with a percentage of 88.75% at 7 days/168 hours after application. The high percentage of mortality and efficacy of dragon scale fern leaf herbal solution against aphid is due tothe influence of compounds contained in the dragom scale fern leaf solution, namely flavonoids which are toxic (kill) to aphid pests. Based on the Analysis of variance which was then carried out with a further DMRT test at a level of 5%, it showed that there was a significant difference in each dose of dragon scale fern leaf herbal solution Keywords : dragon scale fern, mortality, aphid